PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL ANTARA PENGUSAHA DENGAN PEKERJA (ANALISIS PUTUSAN NO. 1/PDT.SUS-PHI/2022/PN PDG) - Angelia, Rina Rahma Ornella; Desmon, Andi; Rahmi, Rahmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Termination of Employment (PHK) refers to the end of an employment relationship as regulated in Indonesian labor law. Dismissal may occur for various reasons, including company efficiency. This article analyzes Decision No. 1/Pdt.Sus-PHI/2022/PN Pdg using a normative juridical approach and qualitative analysis of secondary data. The dispute was first mediated by the Manpower Office but failed, leading to litigation in the Industrial Relations Court. The judges divided their considerations into exceptions, provisional claims, and the main case. They rejected the exception and the provisional claim, declaring the dismissal legally valid. The recognized period of employment was limited to six months due to the legal separation of two companies. Out of eight claims, three were granted, four rejected, and one set aside.Keywords: Termination of Employment; Industrial Relations Dispute.